(untitled) (Indian Journal of Arid Horticulture, 2025)
Aonla is non-climacteric fruit and each year a considerable proportion of aonla fruits are lost through spoilage mainly due to their faulty techniques of storage. Proper storage extends the period of availability of aonla by arresting the metabolic deterioration caused by fungal and microbial activities. In recent years, techniques which are commercially cheaper and require no energy have been developed to retain post-harvest quality of fruits and vegetables for longer period. Proper packaging of fruits and vegetables play a decisive role in reducing the post-harvest losses. keeping the above facts in view, present investigation entitled "Post-harvest effect of packaging material, neem leaf extract and fumigation on colour, texture, shriveling and rotting of Aonla (Emblica officinalis)" was undertaken. The physiological loss in colour, texture, shriveling and rotting of "Chakaiya" cultivar of aonla fruit was significantly affected by packaging materials, neem leaf extracts and diphenyl fumigation and their combinations throughout the storage period up to 21 days.